Designing communication-intensive web applications: experience and lessons from a real case - Perrone, Vito (2005)
Who uses requirements engineering and design methodologies besides the people who invented them? Are researchers -at least- actually trying to use them in real-world complex projects and not in "paper project"? In this paper, we dare to recount the experience and the lessons we gained in trying to use seriously and in-depth a requirements engineering method (called AWARE) combined with a conceptual user-centered design method (called W2000) for the development of a real-world web application. The project is recounted through the process followed and the artefacts produced, as well as by crystallizing our experience in using and transferring the method to industry in practical and methodological recommendations.